2020
DOI: 10.1177/2331216520948385
|View full text |Cite
|
Sign up to set email alerts
|

Spectrotemporal Modulation Sensitivity in Cochlear-Implant and Normal-Hearing Listeners: Is the Performance Driven by Temporal or Spectral Modulation Sensitivity?

Abstract: This study examined the contribution of temporal and spectral modulation sensitivity to discrimination of stimuli modulated in both the time and frequency domains. The spectrotemporally modulated stimuli contained spectral ripples that shifted systematically across frequency over time at a repetition rate of 5 Hz. As the ripple density increased in the stimulus, modulation depth of the 5 Hz amplitude modulation (AM) reduced. Spectrotemporal modulation discrimination was compared with subjects’ ability to discr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 46 publications
0
12
0
1
Order By: Relevance
“…This is likely because spectrotemporally modulated stimuli can potentially be discriminated by amplitude modulations, as postulated by Lawler et al (2017), who point out that these modulations will be affected by spectral resolution (as poorer resolution would fill in the amplitude valleys, rendering discrimination more difficult). Consistent with that notion, Zhou et al (2020) found that scores for SMRT had no correlation with static ripple scores ( r 2 = 0.0009), but did have a positive correlation with modulation detection ( r 2 = 0.46), suggesting that the increased success for SMRT does not reflect a more targeted probe of spectral resolution, but rather a pattern of listeners exploiting temporal cues. Thus, even though the SMRT removes edge-frequency intensity differences as a cue, it introduces edge-frequency modulations as a cue that listeners can use to feign spectral resolution.…”
Section: Methodsmentioning
confidence: 62%
See 2 more Smart Citations
“…This is likely because spectrotemporally modulated stimuli can potentially be discriminated by amplitude modulations, as postulated by Lawler et al (2017), who point out that these modulations will be affected by spectral resolution (as poorer resolution would fill in the amplitude valleys, rendering discrimination more difficult). Consistent with that notion, Zhou et al (2020) found that scores for SMRT had no correlation with static ripple scores ( r 2 = 0.0009), but did have a positive correlation with modulation detection ( r 2 = 0.46), suggesting that the increased success for SMRT does not reflect a more targeted probe of spectral resolution, but rather a pattern of listeners exploiting temporal cues. Thus, even though the SMRT removes edge-frequency intensity differences as a cue, it introduces edge-frequency modulations as a cue that listeners can use to feign spectral resolution.…”
Section: Methodsmentioning
confidence: 62%
“…This means that the SMRT results should not be interpreted as a pure measure of spectral resolution, since the experimenter is unable to determine whether spectral or temporal cues were used to perform the discrimination task. Expressing the threshold solely in terms of spectral ripples per octave is therefore potentially misleading, given Zhou et al (2020) findings. Regardless of the perceptual cue used to successfully discriminate dynamic ripples, Fig.…”
Section: Interpreting Results From Previous Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Spectral modulation thresholds in hearing-impaired listeners have been reported to be 5-10 dB worse than for normal hearing (Davies-Venn et al 2015; Summers and Leek 1994), which may agree with the longer reaction times of our hearing-aid simulation compared to normal hearing. A few studies investigated combined spectrotemporal modulation detection thresholds in hearing-impaired listeners, which were often worse compared to normal hearing listeners, especially for low temporal modulation rates (Bernstein et al 2013; Mehraei et al 2014; Zheng et al 2017; Zhou et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Previous study have confirmed that the ability to detect spectrotemporal modulation, covaried in both the temporal and spectral domains, was related to CI users’ speech recognition performance ( Lawler et al, 2017 ). On this basis, some researchers ( Won et al, 2015 ; Zhou N. et al, 2020 ) evaluated the correlation of speech recognition with the spectrotemporal modulation (STM) thresholds while controlling for either temporal or spectral modulation sensitivity, but different conclusions were drawn. Won et al (2015) suggested that that slow spectral modulation rather than slow temporal modulation may be important for determining speech perception capabilities for CI users.…”
Section: Introductionmentioning
confidence: 99%